Conservative Management of Vaginal Hypoplasia - Özlem Dural; Şükran Poyrazoğlu (Galenos Yayincilik, 2020)
In patients with Mayer-Rokitansky-Küster-Hauser syndrome and complete androgen insensitivity syndrome (CAIS), management of vaginal hypoplasia includes non-surgical or surgical vaginal elongation techniques. For these patients, primary vaginal dilation is considered a first-line option to avoid the risks of having surgery and complications that may occur due to these procedures. Non-surgical dilation is a highly successful treatment if treatment is initiated when the patient is emotionally mature and ready. Here, we present a case of CAIS with vaginal hypoplasia managed successfully with non-surgical dilation therapy.